Decision Support System for Selection of Suitable Mariculture Site in the Western Part of Java Sea, Indonesia - Windupranata, W.; Mayerle, R. (ITB Journal Publisher, LPPM ITB, 2009)
Mariculture (marine aquaculture) has been intensified and has created essentialÂ employmentÂ opportunitiesÂ overÂ theÂ lastÂ two-decadesÂ inÂ Indonesia,Â as well as many other countries in the world. This development has negative impact toÂ theÂ environment.Â ConsiderableÂ amountsÂ ofÂ nutrientÂ wasteÂ inÂ dissolvedÂ and particulateÂ formÂ wereÂ releasedÂ byÂ intensiveÂ fishÂ farmingÂ intoÂ theÂ environment throughÂ feedÂ excess,Â solubleÂ fishÂ excretionÂ andÂ faecesÂ production.Â OneÂ ofÂ the first steps toÂ avoid the dangerous environmental impacts is careful site selection toÂ minimizeÂ environmentalÂ impactsÂ arisingÂ fromÂ theÂ farmingÂ activities (sustainability) as well as to guarantee adequate conditions from the operational point of view (suitability).The paper focuses on the development of a Decision Support SystemÂ (DSS) as a tool for the appropriate selection of maricultureÂ Â site location. The DSS is based onÂ physical,Â chemicalÂ andÂ sedimentÂ criteriaÂ asÂ wellÂ asÂ onÂ dataÂ ofÂ conflicting coastal use. The GIS analysis results in a map indicating the suitable areas for the improvedÂ methodÂ ofÂ offshoreÂ cageÂ mariculture.Â InÂ thisÂ study,Â emphasisÂ was placed on finfish species; however the methods and results may be employed for other species as well following some modifications.The DSS was applied for theÂ western part of Java Sea, Indonesia. The data were acquiredÂ fromÂ directÂ fieldÂ measurement,Â numericalÂ modelingÂ andÂ existing informationÂ fromÂ particularÂ agencies.Â NumericalÂ modelingÂ wasÂ usedÂ toÂ obtain spatialÂ andÂ temporalÂ distributionsÂ ofÂ hydrodynamicÂ parametersÂ (i.e.Â current velocitiesÂ andÂ waterÂ levels).Â TheÂ Delft3DÂ modelingÂ systemÂ (DelftÂ Hydraulics, The Netherlands) was employed for this purpose. The DSS was developed under GISÂ applicationÂ ofÂ ESRIÂ®Â ArcGISâ¢Â usingÂ weightedÂ overlayÂ method.Â The resultsÂ showedÂ theÂ adequacyÂ ofÂ theÂ systemÂ forÂ supportingÂ governmental authorities in the implementation, environmental controlling, and estimationÂ of overall carrying capacity for environmental sustainable marine fish farming.